Evaluating the declarations of open defecation free status under the Swachh Bharat (‘Clean India’) Mission: repeated cross-sectional surveys in Rajasthan, India - Kellogg J Schwab; Natalie G Exum; Emma M Gorin; Goutam Sadhu; Anoop Khanna (BMJ Global Health)
Background The most ambitious sanitation campaign to end open defecation (OD) in India came to a close on 2 October 2019 and there are limited independent, robust data to measure its success. We aimed to evaluate Rajasthan’s claim of open defecation free status in March 2018 under the Swachh Bharat Mission (SBM) or ‘Clean India Mission’ by measuring OD trends from 2016 to 2018.Methods We used publicly available data from Performance Monitoring and Accountability 2020, a representative survey with two-stage stratified cluster sampling. Enumeration areas were the primary sampling units selected by the probability proportional to size method. The repeated cross-sectional surveys independently collected household water and sanitation data in Rajasthan (n=20 485). Among households reporting toilet access, the data were pooled across the four rounds for an observational analysis using logistic regression. The primary outcome measure was regular OD among households with access to toilet facilities.Findings Between October 2016 and July 2018 main OD practices in rural Rajasthan households decreased from 63.3% (95% CI 57.0% to 69.6%) to 45.8% (95% CI 38.4% to 53.2%) and in urban households from 12.6% (95% CI 6.0% to 19.1%) to 9.4% (95% CI 4.0% to 14.7%). Households with regular OD occurring despite access to a toilet made up 21.7% (95% CI 16.9% to 26.6%) of rural and 12.1% (95% CI 3.6% to 20.7%) of urban Rajasthan as of July 2018. The multivariate logistic regression revealed that factors related to water stress and sanitation sharing were associated with household members regularly practising OD.Conclusions These data highlight the importance of a continued focus on constructing toilets that are affordable with low water requirements during the next phase of SBM. An independent survey that can provide robust estimates of OD is needed to monitor progress of toilet construction and use.